BREAKING SILENCE, SHAPING HISTORY: UNVEILING MARGINALIZED FEMALE WAR-CRIME SURVIVORS’ VOICES: Received: 7th August 2023 Revised: 13th December 2023, 18th December 2023 & 21st December 2023 Accepted: 14th September 2023 - Bhaswati Bhattacharjee (PEOPLE: International Journal of Social Sciences, 2024)
This paper is the synopsis of an ongoing qualitative research project on an intersectional and biopolitical analysis of selected war memoirs written by marginalized female war crime survivors. The primary object of this research is to explore the layers of subjectivity as expressed through the memoirs by women who, in different corners of the world, were subjected to different forms of war crimes during the late twentieth and the twenty-first century. The research paper aims to find whether these life-writings should be recognized only as chronicles of their silent sufferings or as bold proclamations of their resistance against the biopolitical oppressions they were exposed to. In order to do so, a theoretical framework comprising intersectionality and biopolitics will be used according to which the selected memoirs will be critically analyzed. The proposed research will follow a research methodology that is descriptive, correlational, analytical, and exploratory in approach. The primary findings reveal the historical trajectory of women’s autobiographical writings related to war and conflicts, identifying the scarcity of such narratives that underscores the challenges faced by survivors in documenting their experiences. The expected outcome is to offer a counter-narrative to official war stories, demonstrating the efficacy of testimonial life-writings from marginalized individuals as human rights activism tools, with potential implications for policy-making, advocacy against sexual violence in conflict zones, and contributing evidence for prevention, justice, and support initiatives, while also highlighting ethical challenges and paving the way for further studies on the intersectional and biopolitical dimensions of sexual violence.